ENGINEERING SUPPLY INFORMATION SYSTEMS BY APPLICATION OF THE METHODS OF ECONOMIC ORDER QUANTITY (EOQ) AT THE SUPERMARKET (CASE STUDY: SAHABAT KITA SWALAYAN) - Istiqomah, Aini; Muslim, Istianah (Jurnal Pilar Nusa Mandiri, 2020)
Sahabat Kita Swalayan is a supermarket located in the city of Bangkinang. The supermarkets have some of the drawbacks of sales, purchases, and supply systems. The frequent losses at this market are due to overstocked and stocked stores. The market also has no record of sales and purchase, so there is no accounting for obvious items. Furthermore, the supermarket owner who makes reservations to the supermarket by mere estimates fails to notice the supply. That way, the stock in the cellar will be overstocked and out of line with the proper sales target. To know the optimum number of purchases and the exact time of repurchase of goods, a system of supply was developed using a method of the economic order quantity (EOQ). The method of the economic order quantity (EOQ) was used to identify the number of ordering optimum stock items. By using reorder points (ROP), it can define the limit of what is in store. Furthermore, the system uses the single exponential smoothie method to predict sales figures. The study led to an undeveloped supply information system that can be implemented in the process of our friend's supermarkets that can be used by the supermarket owner and employee. It is hoped that because of this system, it is possible to help supermarkets maintain pen control.